Akselerasi Ekonomi Umat: Analisis Peran Koperasi Syariah dalam Bingkai Maqashid Syariah - Hartono Hartono; M. Imamuddin; Awaluddin Awaluddin; Rika Widianita; Yenty Astari Dewi; Septria Susanti; Santi Deswita; Cahya Agung Purnama; Ariyun Anisah (KOLONI, 2026)
This study aims to analyze the strategic role of Sharia Cooperatives in improving the economy and welfare of the people through an approach that is in line with Islamic principles. As microfinance institutions, Sharia cooperatives have a unique function that integrates commercial and social aspects to create economic justice. The research method used is a literature review with content analysis techniques on various scientific literature, financial reports, and relevant policy documents. The results of the study indicate that Sharia cooperatives play a role as a driving force for the people's economy by empowering MSMEs with a fair and transparent profit-sharing financing scheme. In addition, the integration of ZISWAF funds in cooperative operations has proven effective as a social safety net for the poor. This study concludes that the welfare of the people generated by Sharia cooperatives includes material and spiritual dimensions in accordance with the Maqashid Sharia indicators. However, challenges in the form of service digitalization and strengthening Sharia compliance remain crucial aspects that must be improved. Synergy between professional governance, technology adaptation, and government regulatory support is essential to optimize the potential of Sharia cooperatives. This study provides theoretical contributions to the development of Islamic economics and practical recommendations for managers in realizing an inclusive, independent, and sustainable economic order for all levels of society.